(untitled) (Journal of Medical & Health Sciences Review, 2025)
Diabetes mellitus is a major disease that causes death and disability all over the world and there are different complexities in the treatment of this disease. From the previous few years, multidrug resistance (MDR) in patients with diabetes mellitus has been increasing day by day and its effects on multiple organs. The risk factor of diabetes mellitus and diabetic foot ulcer is projected to increase by more than 50% in the next decade due to a rapid increase in multi-drug resistance (MDR) issues. The aim of this study was to estimate the prevalence of multi-drug resistant bacteria in diabetic foot ulcer infections by pooling the published that have reported the MDR-DFU prevalence the better control and prevention of the MDR-DFU infections.This study was performed website based using the different electronic databases including the PubMed and the Google scholar. In this study, articles that were published between January 2013 to January 2023 were included. Data from relevant articles were extracted and statically examines was conducted using STATA version 14, the metaprop command was used to retrieve the relevant data. A total 80 articles were identified through electronic databases; of all those 80 studies, 40 statified our inclusion criteria. The forest plot shows that the joint occurrence of the MDR-DFU was 1.55 (95 cl: 1.43-1.67). The total heterogeneity was important, as shown by the values of 12=99.81%, p= 0.00, and momentous ES=0 (z=24.37, p=0.00). More information available about the prevalence and the occurrence of the Multi-drug resistant bacteria in diabetic foot ulcer infections annually. About the prevalence of MDR of DFU in Antarctica, there are no information available. Surveillance is serious to better understand the annual MDR of DFU weight to improve the national and international level.